Understanding the by-product formation potential during phenol oxidation from in-situ electro-generated radicals by microalgae harvesting. Issue 22 (2nd October 2021) - Singh, Hariraj; Kumar, Niwas; Mishra, Brijesh Kumar
ABSTRACT: Advanced oxidation processes have gained colossal attention owing to the prospect of accessible mineralization, but by-product formation and its toxicity evaluation are still inconclusive. The present study demonstrated the performance of electrochemical oxidation process supported with graphite electrodes for the oxidation of phenol from modulated coke oven wastewater. The results suggested that the hydrogen peroxide along with the in-situ synthesized oxidizing agents has the ability to increase the phenol mineralization 1.5 times and by-product toxicity potential on microalgae, Scenedesmus sp . CBIIT(ISM) also revealed that chlorophyll-a synthesis has increased after the electro-oxidation process in coke oven wastewater. The experimental results for phenol mineralization and by-product formation were validated using a mass spectrophotometer. GRAPHICAL ABSTRACT: UF0001